2017
DOI: 10.1111/jvh.12807
|View full text |Cite
|
Sign up to set email alerts
|

Immunotherapy for hepatitis B in the direct acting antiviral era: Reevaluating the thymosin α1 efficacy trials in the light of a combination therapy approach

Abstract: Summary Hepatitis B virus (HBV) causes both acute and chronic hepatitis and infects large numbers of individuals worldwide. Unfortunately, prediction of typical clinical outcome is problematic and there is considerable variability in the frequency, duration and severity of disease progression. The mainstay of HBV treatment is directed towards the suppression of HBV replication by nucleos(t)ide analogs (NUCs). The use of immunomodulators such as α‐Interferon and thymosin α1 can, in select patients, results in e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 37 publications
1
18
0
Order By: Relevance
“…In vitro experiments showed that Tα1 induced the maturation of thymocytes, stimulated differentiation into active T cells and functional recovery of T cells [32]. In vivo experiments verified that Tα1 was associated with the up-regulating activity of natural killer cell in CHB patients [8]. Our results demonstrated that ETV plus Tα1 combination therapy could provide additional benefits of the virological and serological response over ETV monotherapy, which is accorded with previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…In vitro experiments showed that Tα1 induced the maturation of thymocytes, stimulated differentiation into active T cells and functional recovery of T cells [32]. In vivo experiments verified that Tα1 was associated with the up-regulating activity of natural killer cell in CHB patients [8]. Our results demonstrated that ETV plus Tα1 combination therapy could provide additional benefits of the virological and serological response over ETV monotherapy, which is accorded with previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, cirrhosis is also accompanied with serious immunodysfunction, which parallelly presents chronic systemic inflammation and immune inhibition [6]. The present mainstay of HBV treatment is the repression of HBV replication by nucleos(t)ide analogs (NAs), such as entecavir (ETV), lamivudine (LAM) and tenofovir disoproxil fumarate (TDF), and supplementing with the immune-mediated agents such as α-Interferon and Tα1 [7,8]. Theoretically, the strong immune response is conducive to viral suppression and clearance.…”
Section: Introductionmentioning
confidence: 99%
“…It was showed in vitro experiments that Tα1 could inhibit the production of in ammatory cytokines such as TNF-α and potentiate immunocellular function via inducing the maturation of T-cells and up-regulation of CD4+, CD8+ T cells and natural killer (NK) cells [32]. It was veri ed in vivo experiments that Tα1 was associated with the activation of NK cells in patients with CHB [8]. Our results demonstrated that ETV plus Tα1 combination therapy could provide additional bene ts in the inhibition of HBV DNA and negative conversion of HBeAg over ETV monotherapy, but the negative conversion rate of HBsAg was similar between the 2 treatment approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Thα1 is known as an effective therapeutic peptide for the treatment of some diseases . The major actions of this peptide are activation of cytokines, chemokines, and possessing antifungal as well as antibacterial effects .…”
Section: Discussionmentioning
confidence: 99%